2015
DOI: 10.1039/c4tc02837f
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation-controlled vacancy formation in light-emitting wide-band-gap oxide nanocrystals in glass

Abstract: Light emission of nanocrystals (NCs) can depend not only on NC size but also -and even more importantly in wide-band-gap NCs -on the occurrence of optically active sites, such as donor-acceptor pairs (DAPs).Here, we demonstrate that controlling the thermo-chemical conditions of NC nucleation when NCs are forming in a solid host -an approach often used for driving NC size dispersion -can be an innovative strategy for tailoring DAP population. Our data show that light emission from DAP recombination and decay in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In summary, the analysis of DSC and XRD data shows that Ni and Ti doping can influence the glass nanocrystallization, with effects on size and concentration of γ‐Ga 2 O 3 NCs. Therefore, as NC size affects the balance between V O and V Ga sites inside each NC, we can expect a NC size‐related effect of doping on the donor–acceptor light‐emission properties of NCs. Furthermore, Ti 4+ and Ni 2+ ions substituting Ga 3+ can also play an even larger and more direct role in DAP and defect‐related optical emissions of the nanophase, provided that they enter into the NCs so as to modify the donor and acceptor populations by heterovalent substitution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the analysis of DSC and XRD data shows that Ni and Ti doping can influence the glass nanocrystallization, with effects on size and concentration of γ‐Ga 2 O 3 NCs. Therefore, as NC size affects the balance between V O and V Ga sites inside each NC, we can expect a NC size‐related effect of doping on the donor–acceptor light‐emission properties of NCs. Furthermore, Ti 4+ and Ni 2+ ions substituting Ga 3+ can also play an even larger and more direct role in DAP and defect‐related optical emissions of the nanophase, provided that they enter into the NCs so as to modify the donor and acceptor populations by heterovalent substitution.…”
Section: Resultsmentioning
confidence: 99%
“…Starting from those results, some recent studies have demonstrated that DAP concentration per NC can be controlled, to some extent, by tailoring the NC size and, consequently, the concentration of V O per NC at fixed oxygen deficiency in the nanophase. This result has been obtained either in nanopowders of selected size, or in grown‐in‐glass NCs by thermal tuning of the nucleation process . Nevertheless, V O and V Ga are expected to be also influenced by doping with ions, substituting Ga 3+ with different oxidation states, as demonstrated in quantum dot (QD) colloids, so giving the prospect of a size‐independent method—driven by charge neutrality—to control the broadband visible‐light emission of Ga oxide at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was used as it can more accurately predict the temperature dependence of the nucleation rate rather than the peak height method in the case of considerable overlapping of the nucleation and growth processes [28]. The heat treatments were performed by placing the samples into the muffle furnace at room temperature, heating them at a rate of 10 °C/min up to 595 ºC (accuracy ±2 ºC) and holding for 2.5, 3.5, 4.5, 6.5 or 8.5 h. The treatment temperature was chosen according to previous data on similar glass indicating the occurrence of nucleation process in that range of temperatures [26].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, low-alkali gallium germanosilicates can be obtained at temperatures lower than 1500 ºC and after doping with Ni 2+ also demonstrate broadband NIR emission with comparable quantum yield [23][24][25]. Two-step heat treatment of Ni-free low-alkali gallium germanosilicates was shown to have notable impact on size and number of nanocrystals (NCs) of spinel-like gallium oxide precipitated in the glass matrix [26]. In regard to Ni 2+ -doped germanosilicates, only one-step heat treatment has been used up to now, and a strong correlation has been revealed between the number of Ni 2+ ions per NC and the integrated intensity of the related broadband NIR emission [24].…”
Section: Introductionmentioning
confidence: 99%